Development of plant diversity flipbooks integrated local wisdom - Sirait, Silvia Hanna Kusuma; Sremere, Friana Martina; Nunaki, Jan Hendriek; Tuwo, Mustika (Inornatus: Biology Education Journal, 2024)
For plant diversity course, teaching materials in the form of interactive e-modules were not yet available. The diversity of sago plants has been compiled in the form of a supplementary book, but was limited to the printed type. This research aimed to develop flipbook-based e-module teaching materials integrated with local wisdom in the plant diversity course. The e-module contains local wisdom about the diversity of sago plants which were differentiated based on the color of the leaf shoots and the varying shape of the midrib as well as the use of the local (regional) language of the Tehit Kna tribe. E-module was expected to be a bridge in the process of digitizing teaching materials. The data source for this research was 9 active students from the Biology Education Department, odd semester for the 2023/2024 academic year. This research was conducted at the Department of Biology Education, University of Papua Manokwari and used the R&D research method with the ADDIE model but was limited to the following stages: Design, design, framework and preparation of the e-module from the front view, the contents of the book to the back cover of the book; Development, validation of flipbook-based e-module teaching material prototypes by media experts; and Evaluation, assessing each stage until the product produced in the form of an interactive e-module based on a flipbook integrated with local wisdom was declared valid and practical. The research results show that the e-module was very valid (96.5%) and very practical (95.56%).